PENDIDIKAN MULTIKULTURAL MENUJU MASYARAKAT BERMARTABAT - Bunyamin Bunyamin (Universitas Muhammadiyah Prof Dr Hamka, 2016)
This research aims to reveal the depth of multicultural education. This study uses qualitative descriptive approach situational analysis. These results indicate the idea of forming system using the concept of multicultural education. , The results of this study can be applied in learning syllabus Religious Education / Akhlaq for high school / boarding school.